إجراءات الدعوى الضريبية في ظل التشريع الجزائري - بن زيـان سـارة بن طيب نبيلة (جامعة محمد بوضياف المسيلة, 2020)
إن دراسة موضوع إجراءات الدعوى الضريبية في التشريع الجزائري, من بين أكثر المواضيع انتشارا في المجال الضريبي, مما يطرح الكثير من النزاعات الناشئة بين المكلف بالضريبة والإدارة الضريبية. حيث تم تقسيم هذا الموضوع إلى فصلين: تناولنا في الفصل الأول " إجراءات الدعوى الضريبية أمام إدارة الضرائب", فتتمثل في الحد في المنازعات الضريبية بين المكلف بالضريبة والإدارة الضريبية, فالمشرع منح المكلف بالضريبة عدة طرق بدءا من التظلم الإداري المسبق أمامها باعتبارها الجهة مصدرة القرار الذي يسمح بتبادل وجهات النظر بين المكلف وإدارة الضرائب من أجل استدراك أخطائه, وفي حالة عدم رضا المكلف بقرار مدير الضرائب بالولاية منحه المشرع الطعن أمام جهة أخرى متمثلة في لجان الطعن الإدارية, كما أن اللجوء إليها اختياري قبل اللجوء إلى القضاء.أما الفصل الثاني فقد تناولنا "إجراءات رفع الدعوى الضريبية أمام الغرفة الإدارية" بدءا بشروط رفعها إلى إجراءات سيرها, وإجراءات الطعن أمام مجلس الدولة , الاستئناف والنقض باعتبارها الوسيلة التي يخولها القانون للمطالبة بحقوق مستها أعمال إدارة الضرائب. The study of the subject of tax lawsuit procedures in the Algerian legislation is among the most widespread topics in the tax field, which raises many of the disputes arising between the taxpayer and the tax administration. As this issue was divided into two chapters: In the first chapter, we dealt with "tax lawsuit procedures in front of the tax administration", which is represented in limiting tax disputes between the taxpayer and the tax administration. The legislator granted the taxpayer several ways starting with the prior administrative grievance before it as the issuing authority which It is permitted to exchange views between the taxpayer and the tax administration in order to redress his mistakes, and in the event that the taxpayer does not accept the state’s tax director’s decision to grant the legislator the appeal before another authority represented in the administrative appeal committees, and resorting to it is optional before resorting to the judiciary. As for the second chapter, we dealt with " Procedures for filing a tax lawsuit in front of the administrative chamber "starting with the conditions for filing it with the procedures for its conduct, and the procedures for appeal before the State Council, appeal and cassation as the means authorized by law to claim rights touched by the work of the tax administration
Keywords: الدعوة الضريبية -التشريع الجزائري